Channel Catfish Hatchery Production Efficiency Using a Vertical‐Lift Incubator (the See‐Saw) at Various Egg Loading Rates. (19th March 2013) - Torrans, Les; Ott, Brian; Jones, Robert "Shorty"; Jones, Robert
Abstract: Channel Catfish Ictalurus punctatus spawns are typically incubated in 0.25‐in‐mesh baskets suspended in water that is agitated with paddles positioned between the baskets. We previously tested a vertical‐lift incubator (the "See‐Saw") using Channel Catfish spawns. When loaded with spawns at rates higher than recommended for traditional paddle‐type incubators, as often occurs during the peak of the spawning season, survival to the swim‐up stage was significantly (2.3 times) higher with the See‐Saw than with traditional incubators. This project examined the effect of spawn loading rate and added oxygen on fry production with the See‐Saw. In study 1, See‐Saws were loaded with 15.0 ± 0.1 lb (mean ± SE; 219, 825 eggs), 30.1 ± 0.1 lb (446, 055 eggs), 45.1 ± 0.1 lb (668, 206 eggs), or 60.1 ± 0.1 lb (891, 157 eggs) of spawns per trough. Water flow averaged 2.1 gal/min—roughly 40% of the rate recommended for paddle‐type incubators. Swim‐up fry production increased in proportion to egg loading density up to 45 lb/trough, with the 15‐, 30‐, and 45‐lb loading rate treatments producing 132, 658, 263, 828, and 429, 422 swim‐up fry, respectively. However, the 60‐lb treatment produced only 417, 237 swim‐up fry. Survival to the swim‐up stage in the 15‐, 30‐, and 45‐lb treatments averaged 60 ± 9, 59 ± 6, and 64 ± 4%, respectively, but survival to swim‐up in the 60‐lb treatment averaged only 46 ± 8%. In study 2, the addition of purified oxygen to See‐Saw incubators loaded with 36 spawns/trough (∼45 lb/trough) increased the DO concentration by 4.0 ppm (to 125% air saturation) but had no effect on survival to swim‐up. The See‐Saw incubator can effectively incubate up to 45 lb of spawns (670, 000 eggs)—up to three times as many eggs as traditional paddle‐type incubators—while using less than half the water; thus, the See‐Saw incubator can provide significant savings in space, water, and energy use.